Sistem Pendukung Keputusan Pemilihan Bimbingan Belajar Unggulan Kota Tanjungpinang dengan Metode Promethee II - Liza Safitri; Aurora Elsa S F; Willy Setiawan (LPPM Sekolah Tinggi Teknologi Indonesia Tanjung Pinang, 2023)
This study aims to create a decision support system to determine the selection of leading tutoring institutions in Tanjungpinang City by applying the Promethee II method from several samples according to existing method procedures, from the data collection that has been carried out, several tutoring criteria are obtained and then calculations are carried out using the stages contained in the Promethee II method. The application is built based on a website, the aim is to help parents to select excellent tutoring institutions, check reports and election results using the website. It is hoped that this research can be one of the solutions to determine the selection of leading tutoring institutions in Tanjungpinang City.